Molecular evidence supporting the expansion of the geographical distribution of the Brazilian cownose ray Rhinoptera brasiliensis (Myliobatiformes: Rhinopteridae) in the western Atlantic - Palacios-Barreto, Paola; Cruz, Vanessa P. [UNESP]; Foresti, Fausto [UNESP]; De Rangel, Bianca S.; Uribe-Alcocer, Manuel; Díaz-Jaimes, Píndaro (Magnolia Press, 2017)
The genus Rhinoptera is composed of eight species widely distributed in tropical, subtropical and temperate coastal waters, which inhabit bays, estuaries and river mouths. Cownose ray Rhinoptera bonasus has been reported to inhabit the Western Atlantic including the Gulf of Mexico and the Caribbean, whereas the Brazilian cownose ray R. brasiliensis has been considered endemic to the coast of Brazil. Recent reports of R. brasiliensis in the Gulf of Mexico bring about the question of whether the species has a wider range than previously reported. Here, the mitochondrial genes COI, Cytb, NADH2 and the nuclear gene RAG1 were used to distinguish among species and to confirm the presence of R. brasiliensis in the Gulf of Mexico. R. brasiliensis specimens collected along the southern Gulf of Mexico showed a remarkable genetic and morphological affinity when compared with R. brasiliensis specimens from Brazil, supporting the presence of the species in Mexico (from Veracruz through Campeche) and providing evidence that its distribution ranges from Brazil to the Caribbean Sea and the Gulf of Mexico. Both species overlap geographically to a large degree, leading to a reassessment of their conservation status. Our results also show that R. bonasus distribution in the Gulf of Mexico may be restricted to the northern portion, in US waters.
Keywords: Batoids; Cownose rays; Gene divergence; Range expansion